First record of the rendezvous fish, Polymetme corythaeola (Alcock, 1898), in the Mediterranean Sea. (29th October 2021) - Lombarte, Antoni; Balcells, Marc; Barría, Claudio; Azzurro, Ernesto
Abstract: The occurrence of the rendezvous fish, Polymetme corythaeola (Alcock, 1898) in Mediterranean Sea is here reported for the first time. A single individual of this benthopelagic fish was caught in February 2020 during a scientific trawl survey. The specimen was collected at a depth of 369 m (upper slope) in the Gulf of Roses (Catalonia, north‐western Mediterranean). This circumglobal species could have naturally expanded its distribution through the Strait of Gibraltar, but we cannot totally exclude that its Mediterranean occurrence has been overlooked thus far. This finding highlights the importance of continuous monitoring of Mediterranean deep‐sea habitats for a better understanding of their diversity and ongoing transformation.